Effects of heat treatment on the intermetallic compounds and mechanical properties of the stainless steel 321–aluminum 1230 explosive-welding interface - Shiran, Mohammadreza Khanzadeh Gharah; Khalaj, Gholamreza; Pouraliakbar, Hesam; Jandaghi, Mohammadreza; Bakhtiari, Hamid; Shirazi, Masoud (International journal of minerals, metallurgy and materials, 2017)
The effects of heat treatment on the microstructure and mechanical properties of intermetallic compounds in the interface of stainless steel 321 explosively bonded to aluminum 1230 were investigated in this study. Experimental investigations were performed by optical microscopy, scanning electron microscopy, and microhardness and shear tensile strength testing. Prior to heat treatment, increasing the stand-off distance between samples from 1 to 2.5 mm caused their interface to become wavy and the thickness of intermetallic layers to increase from 3.5 to 102.3 μm. The microhardness increased from HV 766 in the sample prepared at a stand-off distance of 1 mm to HV 927 in the sample prepared at a stand-off distance of 2.5 mm; in addition, the sample strength increased from 103.2 to 214.5 MPa. Heat treatment at 450°C for 6 h increased the thickness of intermetallic compound layers to 4.4 and 118.5 μm in the samples prepared at stand-off distances of 1 and 2.5 mm, respectively. These results indicated that increasing the duration and temperature of heat treatment decreased the microhardness and strength of the interface of explosively welded stainless steel 321?Al 1230 and increased the thickness of the intermetallic region.